2019
DOI: 10.18001/trs.5.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Alternative Tobacco Products in Unaccompanied Homeless Youth

Abstract: Objectives: This study examined perceptions of factors that influence use and non-use of Alternative Tobacco Products (ATPs) among unaccompanied youth experiencing homelessness. Methods: Focus groups were conducted with 30 homeless 18–24 year olds (80% men, 50% Hispanic, 30% Black, 17% White, 20% multi-racial/other) recruited from drop-in centers in Los Angeles. Discussion focused on several ATPs (hookah, electronic cigarettes/vaping devices, cigarillos/little cigars, smokeless tobacco, snus, natural cigaret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…30,31 Perceptions of ENDS and hookah as being less harmful 52,53 and as having a more palatable taste 54,55 are not only associated with use in the young adult population in general, but qualitative work has found that these are cited as reasons for using these products by young tobacco users experiencing homelessness. 56 Taken together, these findings suggest that perceptions and beliefs about ENDS and hookah are, in part, derived from exposure to advertising with themes that emphasize flavor and/or harm reduction. Or alternatively, that homeless youth who intend to use ENDS and/or hookah in the future believe that these products are less harmful and/or have palatable flavors and seek out advertising for these products that is LGBQA, lesbian, gay, bisexual, questioning, or asexual; SE, standard error.…”
Section: Discussionmentioning
confidence: 82%
“…30,31 Perceptions of ENDS and hookah as being less harmful 52,53 and as having a more palatable taste 54,55 are not only associated with use in the young adult population in general, but qualitative work has found that these are cited as reasons for using these products by young tobacco users experiencing homelessness. 56 Taken together, these findings suggest that perceptions and beliefs about ENDS and hookah are, in part, derived from exposure to advertising with themes that emphasize flavor and/or harm reduction. Or alternatively, that homeless youth who intend to use ENDS and/or hookah in the future believe that these products are less harmful and/or have palatable flavors and seek out advertising for these products that is LGBQA, lesbian, gay, bisexual, questioning, or asexual; SE, standard error.…”
Section: Discussionmentioning
confidence: 82%
“…It remains to be determined what impact a menthol or flavor ban may have on co-use of tobacco and cannabis and use of non-combustible tobacco products. Studies suggest that YEH have misperceptions about the relative risk of non-combustible tobacco compared with cigarettes [ 16 ], which could perpetuate the use of combustible products, even if menthol is banned. Correcting for harm misperceptions may be needed through counseling.…”
Section: Discussionmentioning
confidence: 99%
“…These users were heavier users of tobacco and marijuana compared to those who used tobacco alone or co-used (used both simultaneously or within the same time-period), but not co-administered; they also tended to experience more severe homelessness and other risk factors like depression. Little cigars and cigarillos are commonly viewed among young adults experiencing homelessness as a discreet way to smoke marijuana [ 16 ]. About three-quarters of cigar smoking high school youth in Cuyahoga County, Ohio in 2013 reported concurrent past 30-day marijuana use, about half reported “freaking” their cigar (removing the filter paper from the cigar and repacking), and two-thirds reported using blunts [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Youth experiencing homelessness have different perceptions of various non-cigarette tobacco products. A study found that perceptions of EVPs were generally negative due to their cost and a perception that EVPs may be just as harmful as cigarettes (11). Smokeless tobacco was also viewed negatively, as was snus, with homeless youth having mixed opinions about whether they are more or less harmful than regular cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…A study of youth and young adults experiencing homelessness in Los Angeles (LA) County, California found that about 90% of tobacco users consumed tobacco and marijuana together (10), These users were heavier users of tobacco and marijuana compared to those who used tobacco alone or co-used, but not co-administered; they also tended to experience more severe homelessness and other risk factors like depression. Little cigars and cigarillos (LCCs) are commonly viewed among young adults experiencing homelessness as a discreet way to smoke marijuana (11). About three-quarters of cigar smoking high school youth in Cuyahoga County, Ohio in 2013 reported concurrent marijuana use, about half reported "freaking" their cigar (removing the lter paper from the cigar and repacking), and two-thirds reported using blunts (removing tobacco contents from a cigar and replacing or mixing with marijuana) (12).…”
Section: Introductionmentioning
confidence: 99%